Copyright for archivists and records managers / Tim Padfield. - Padfield, Timothy (Facet copyright classics, 2015)
The fifth edition of this respected work has been extensively revised and updated to include: a description of the major changes to copyright exceptions and limitations for libraries and archives including the changes to permit preservation copying and copying for users of any kind of work, a simplification of the declarations required from users and a new exception permitting onsite access to digital material; a description and discussion of the new schemes for orphan works; a description of the other changes to exceptions for copyright and performer's rights, notably education; quotation; caricature, parody and pastiche; text and data mining; disability; and private copying; a revision of the views expressed on the exhibition of literary, dramatic and musical works; an explanation of why a digital photograph, consisting of a numerical file, is still an artistic work; a description of the changes in duration for sound recordings and especially for sound recordings of performances and for copyright in songs; analysis of new copyright legislation in the Channel Islands and other British overseas territories; an explanation of how national courts decide whether they have jurisdiction over the infringement of copyright on the internet; a description of changes to Crown copyright licensing and the licensing of public sector information; a new section giving links to useful websites; consideration of the many copyright cases that have come before the courts the last few years that have provided help with the interpretation of many aspects of the legislation. Some notable examples are on the meaning of 'transient and incidental', 'scientific research', 'parody' and 'originality'; whether hyperlinking infringes; the importance of a signature on an assignment; the terms that may be implied into a licence; and the relationship between the rights of a copyright owner and freedom of speech.